Association of Carotid Artery Disease with Various Risk Factors Among Patients Presenting with Ischemic Stroke - Nizami, Muhammad Asif; Yousaf, Muhammad Ali; Liaqat, Jahanzeb; Nawaz, Khurram Haq; Hashmat, Asif (Pakistan Armed Forces Medical Journal, 2022)
OBJECTIVE: To study the association of carotid artery disease with various risk factors among patients presenting with ischemic strokeSTUDY DESIGN: Analytical studySETTING: Department of neurology Pak Emirates Military Hospital RawalpindiDURATION OF STUDY: Eight months, from 1st July 2019 to 29th February 2019PATIENTS AND METHODS: A total of 300 patients with ischemic stroke diagnosed by the consultant neurologist were included in this study. A consultant radiologist assessed the presence of clinically significant carotid artery stenosis by performing an ultrasound examination of carotid region. Relationship of age, gender, presence of diabetes mellitus, presence of hypertension and tobacco smoking was assessed with the presence of carotid artery stenosis among the patients of ischemic stroke.Results:  Out of 300 patients of stroke assessed through ultrasound Doppler, 171 (57%) showed the presence of significant carotid artery stenosis while 129 (43%) had no clinically significant stenosis. Statistical analysis revealed that presence of diabetes mellitus and hypertension had a statistically significant relationship (p-value